Meta-Analysis of the Effect of High-Intensity Interval Training in Increasing High-Density Lipoprotein Levels in Type 2 Diabetes Mellitus Patients - Adelita, Sela Putri; Pamungkasari, Eti Poncorini; Murti, Bhisma (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Diabetes mellitus is one of the second biggest health problems. The International Diabetes Federation said that diabetes currently affects 382 million people worldwide, with type 2 diabetes mellitus (DM) being the largest prevalence of 85-95% of the diabetes population. This study aimed to estimate the effect of high-intensity interval training (hiit) on increasing levels of high-density lipoprotein in patients with type 2 diabetes mellitus based on the results of several previous studies.Subjects and Method: This study was a meta-analysis and systematic study, with the following PICO Population =type 2 diabetes mellitus patients aged 35-65 years. Intervention=HIIT. Comparison = No HIIT. Outcome = increased levels of high-density lipoprotein. The articles used in this study were obtained from several databases, including PubMed, ScienceDirect, and Google Scholar. The keywords for finding articles were: